Control of root growth and development by reactive oxygen species. (February 2016) - Tsukagoshi, Hironaka
Highlights: Reactive oxygen species (ROS) act as signaling molecules. ROS is regulating root meristem activity, tip growth of root hair, and lateral root development. Complex avenues of cross talk exist between ROS and other molecular signals, such as plant hormones for root development. Abstract : Reactive oxygen species (ROS) are relatively simple molecules that exist within cells growing in aerobic conditions. ROS were originally associated with oxidative stress and seen as highly reactive molecules that are injurious to many cell components. More recently, however, the function of ROS as signal molecules in many plant cellular processes has become more evident. One of the most important functions of ROS is their role as a plant growth regulator. For example, ROS are key molecules in regulating plant root development, and as such, are comparable to plant hormones. In this review, the molecular mechanisms of ROS that are mainly associated with plant root growth are discussed. The molecular links between root growth regulation by ROS and other signals will also be briefly discussed.